2012
DOI: 10.1016/j.cageo.2011.07.009
|View full text |Cite
|
Sign up to set email alerts
|

3D multiple-point statistics simulation using 2D training images

Abstract: a b s t r a c tOne of the main issues in the application of multiple-point statistics (MPS) to the simulation of threedimensional (3D) blocks is the lack of a suitable 3D training image. In this work, we compare three methods of overcoming this issue using information coming from bidimensional (2D) training images. One approach is based on the aggregation of probabilities. The other approaches are novel. One relies on merging the lists obtained using the impala algorithm from diverse 2D training images, creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
115
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(116 citation statements)
references
References 30 publications
1
115
0
Order By: Relevance
“…However, a fundamental challenge for the use of MPS for 3-D hydrogeological modelling lies in the difficulty in producing realistic 3-D TIs (e.g. Pérez et al, 2014;Ronayne et al, 2008), and most of the studies in the literature are therefore based on 2-D or quasi-3-D TIs (Jha et al, 2014;Comunian et al, 2012;Feyen and Caers, 2006). Much research has demonstrated the potential of the MPS to simulate 2-D patterns Y.…”
mentioning
confidence: 99%
“…However, a fundamental challenge for the use of MPS for 3-D hydrogeological modelling lies in the difficulty in producing realistic 3-D TIs (e.g. Pérez et al, 2014;Ronayne et al, 2008), and most of the studies in the literature are therefore based on 2-D or quasi-3-D TIs (Jha et al, 2014;Comunian et al, 2012;Feyen and Caers, 2006). Much research has demonstrated the potential of the MPS to simulate 2-D patterns Y.…”
mentioning
confidence: 99%
“…These "copy and paste" methods are simple but certain assumptions need to be invoked. Other methods include complicated statistical simulations such as Comunian et al (2011) and Comunian et al (2012). They used probability aggregation approaches to retrieve statistical information from 2-D TIs which subsequently were applied to simulate a 3-D TI.…”
Section: L He Et Al: Multiple-point Geostatistics In Groundwatermentioning
confidence: 99%
“…AMag data provided a continuous spatial input to the MPS code that does not rely solely on sparse borehole data to constrain the output. Additionally, the existing geological models provided a conceptual understanding, which was found to present an efficient input for MPS algorithms (Blouin et al 2013;Renard 2007) This study is not bound by complex 3D training image problems as detailed in existing literature (Blouin et al 2013;Comunian et al 2011Comunian et al , 2012, as it has been estimated through magnetic modelling at two field sites (Burns et al 2010;Wilson 2011;Comte et al 2012) that the dykes are sub-vertical cuboids, emplaced within the sandstone. Therefore, the spatial distribution in the Z direction was not computed and data were treated as horizontal two-dimensional (2D).…”
Section: Mps Data Preparation: Training Images and Simulation Gridmentioning
confidence: 99%